2016
DOI: 10.1007/s10068-016-0072-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of water-soluble extracts of long-term fermented Doenjang on bone metabolism bioactivity and breast cancer suppression

Abstract: Anti-cancer effects of extracts are usually studied based on methanol extraction focusing on isoflavones, the principal extracted components. In this syudy, effects of water-soluble extracts of long-term fermented containing water-soluble low Mw peptides produced by microorganisms were studied. extracts had effects which arrested the cell cycle, inhibited proliferation, and caused consequential apoptosis in breast cancer cells. water-soluble extracts increased bone density via activation of osteoblast differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Isoflavonoids decrease bone resorption through the OPG/RANKL/RANK pathways, similar to the HSLA and HSHA activity observed in the present study [31]. Previous research has shown that consuming fermented soybean products like natto and doenjang is associated with increased BMD in postmenopausal women [33][34][35]. In the current study, the intake of HSLA and HSHA, among various types of TMDs, effectively prevented BMD loss in OVX rats by reducing bone resorption by decreasing serum PTH concentration.…”
Section: Discussionsupporting
confidence: 86%
“…Isoflavonoids decrease bone resorption through the OPG/RANKL/RANK pathways, similar to the HSLA and HSHA activity observed in the present study [31]. Previous research has shown that consuming fermented soybean products like natto and doenjang is associated with increased BMD in postmenopausal women [33][34][35]. In the current study, the intake of HSLA and HSHA, among various types of TMDs, effectively prevented BMD loss in OVX rats by reducing bone resorption by decreasing serum PTH concentration.…”
Section: Discussionsupporting
confidence: 86%
“…Based on the reviewed in vitro and in vivo studies, apoptotic cell death of experimental cells was triggered by FWG treatment (Koh et al, 2018), by FWNS treatment (Schlörmann et al, 2017), through the activation of death receptor-mediated pathway and tBid-mediated mitochondrial pathway by the FBRE treatment (Horie et al, 2016), mitochondrial-dependent pathway by FRMR treatment (Lee et al, 2013); suppression of cell proliferation by FRMR treatment (Lee et al, 2013), by FWG treatment (Koh et al, 2018), by FWA treatment (Borowicki et al, 2010) by treating with optimally ripened enriched kimchi (Kim et al, 2015), by fermented soymilk treatment (Lai et al, 2013), by treatment with fermented doenjang extract (Seol et al, 2016); cell cycle arrest by FRMR treatment (Lee et al, 2013), by FWA treatment (Borowicki et al, 2010); anti-cancer activity of EFCPE mediated by Caspase-3, MKK3/6, and p38 signaling pathways (Lee et al, 2018); and inhibition of inflammatory reaction by yogurt intake (Del Carmen et al, 2016) are the most possible mechanisms by which fermented foods confer protective activity against cancer occurrence and development. Based on the few clinical studies, consumption of fermented products such as fermented wheat germ extract (Demidov et al, 2008), fermented soy product (Sonoda et al, 2004;Sharp et al, 2005;Wada et al, 2015) improved the health status of the people.…”
Section: Results Of Human Studiesmentioning
confidence: 99%
“…Fermented doenjang extract inhibited the osteoclastic differentiation. The study proved that fermented doenjang extract was packed with anti-proliferative bioactive compounds that could be used to treat breast cancer and also exhibited bone metabolism bioactivity (Seol et al, 2016). Therefore, fermentation duration influences the quality of doenjang in terms of bioactivity and health benefits.…”
Section: In Vitro Studiesmentioning
confidence: 96%
See 1 more Smart Citation
“…For instance, soy products and soy isoflavones could induce apoptosis in both ER+ and ER− breast cancer cells. A water-soluble extract of long-term fermented doenjang (a fermented soybean product in Korea) induced cell cycle arrest, proliferation inhibition, and consequential apoptosis in breast cancer cells [ 64 ]. In addition, growth inhibition and apoptosis were induced by genistein in MCF-7-C3 and T47D cells, through downregulation of the cancerous inhibitor of protein phosphatase 2A, an oncogene found overexpressed in breast cancer [ 65 ].…”
Section: Soymentioning
confidence: 99%